2005
DOI: 10.1128/jvi.79.6.3831-3840.2005
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Pseudorabies Virus UL51 Protein

Abstract: Homologs of the UL51 protein of herpes simplex virus have been identified in all herpesvirus subfamilies, but until now, no function has been assigned to any of them. To investigate function of the UL51 gene product of the alphaherpesvirus pseudorabies virus (PrV), we isolated and analyzed a mutant lacking the major part of the open reading frame, PrV-⌬UL51F, and a rescuant. One-step growth analysis of PrV-⌬UL51F revealed only slightly reduced titers, but plaque size was notably diminished and reached only app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
60
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 41 publications
8
60
0
Order By: Relevance
“…The phenotypes in virion morphogenesis, including aberrant accumulation of unenveloped and partially enveloped virions and the lack of enveloped virions in the cytoplasm and extracellular space, have been suggested to reflect a block in a process(es) for viral secondary envelopment (27,28,51). The results in this study indicated that UL51 and UL14 acted in the same HSV-1 secondary envelopment pathway during HSV-1 replication.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The phenotypes in virion morphogenesis, including aberrant accumulation of unenveloped and partially enveloped virions and the lack of enveloped virions in the cytoplasm and extracellular space, have been suggested to reflect a block in a process(es) for viral secondary envelopment (27,28,51). The results in this study indicated that UL51 and UL14 acted in the same HSV-1 secondary envelopment pathway during HSV-1 replication.…”
Section: Discussionsupporting
confidence: 59%
“…As described above, HSV-1 UL51 and UL14 are conserved throughout the Herpesviridae family (1), raising the interesting possibility that complexes of UL51 and UL14 homologues in other herpesviruses regulate viral secondary envelopment. In support of this possibility, it has been reported that UL51 homologs in alphaherpesvirus PRV and betaherpesvirus HCMV are involved in viral secondary envelopment (27,28). However, the HSV-1 UL51 domain and amino acid residues required for interaction with UL14 are conserved in alpha- herpesviruses but not in beta-and gammaherpesviruses (Fig.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…On the other hand, individual deletions of tegument proteins UL11, UL37, UL47, UL48, and UL51 have all resulted in accumulation of unenveloped cytoplasmic capsids, a finding that suggests a defect in secondary envelopment (133,214,218,226,227). The UL20 membrane protein is a component of virions and plays a role in sorting mature enveloped virions from the site of secondary envelopment to be released from the cell (137).…”
Section: Egressmentioning
confidence: 99%
“…In keeping with its proposed role in virion formation, a number of interactions between tegument proteins among themselves and with other structural proteins have been described in PrV and other herpesviruses (reviewed in references 33 and 34). Electron microscopic studies of cells infected with mutants deleted in tegument proteins US3 (23), UL11 (27), UL16 (20), UL36 (10), UL37 (21), UL47 (28), UL48 (8), and UL51 (22) have documented the relevance of these tegument proteins for morphogenesis of PrV.…”
mentioning
confidence: 99%